Gestational low protein diet in the rat mediates Igf2 gene expression in male offspring via altered hepatic DNA methylation - Gong, Li; Pan, Yuan-Xiang; Chen, Hong (Epigenetics, 2010)
Biological responses to environmental stress, including nutrient limitation are mediated in part by epigenetic modifications including DNA methylation. Insulin-like growth factor II (Igf2) and H19 are subject to epigenetic modifications leading to genomic imprinting. The present study was designed to test the effect of maternal low protein diet on the Igf2/H19 locus in offspring. Pregnant Sprague-Dawley rats were fed diets containing 180 g/kg casein (control) or 90 g/kg (LP) casein with either 1 mg/kg (LP) or 3 mg/kg folic acid (LPF). LP diet increased Igf2 and H19 gene expression in the liver of day 0 male offspring and the addition of folic acid reduced the mRNA level in LPF rats to that of the control group. DNA methylation in Imprinting Control Region (ICR) of Igf2/H19 locus increased significantly following maternal LP diet but rats fed the LPF diet did not exhibit the hypermethylation. The Differential Methylation Region 2 (DMR2) did not show any change in methylation in either LP or LPF rats. The expression of Dnmt1 and Dnmt3a, the members of DNA methyltransferase family, and methyl CpG-binding domain 2 (Mbd2) was significantly increased following the maternal LP diet but did not differ between the control and LPF group. There is a strong correlation between methylation of ICR with the expression of Igf2 and H19. These results suggested that maternal exposure to a low protein diet and folic acid during gestation alters gene expression of Igf2 and H19 in the liver by regulating the DNA methylation of these genes. The DNA methyltransferase machinery may be involved into the programming of imprinted genes through the imprinted control region.